Sense of Community: The Irish Deaf Community - John Bosco Conama (The Irish Association for Applied Linguistics, 2021)
There is a strong perception among members of the Irish deaf community that the community is in gradual decline, with dwindling traditional bases for producing Irish Sign Language (ISL) users. For instance, enrolments in residential schools for the deaf have been declining steadily, and the numbers involved in social, sports and cultural activities in the community have been falling. Technological advances, consolidation of educational policies for deaf children in mainstream education, and individualisation and increased social mobility have also had an impact on how this community operates. However, there is paltry research on how such changes have affected deaf community cohesion, especially in the Irish context. Therefore, this ongoing research entitled Sense of Community – the Irish Deaf Community, seeks to explore the notion and strength of community belonging amongst the deaf community in Ireland. This project report presents the results of one element of this research, i.e. an online survey study conducted in June 2020. Initial analysis of the results of this survey indicate that ISL is one of the primary bonds holding the Irish deaf community together and that issues that divide the community include trustworthiness, feelings of exclusion, and the notion of leadership.